Empowering Students Through Eco-Enzyme Education to Reduce Household Organic Waste - Wibowo, Damar Aji Susilo; Permana, Ilham Aji; Sakti, Achmad Tunjung Prabowo; Norbertus Citra Irawan; Dewi Rahmawati Intan Permatasari (Universitas Tunas Pembangunan Surakarta, 2025)
Indonesia faces a growing challenge in managing household organic waste, much of which originates from kitchen leftovers that are often discarded without proper treatment. Communities lack awareness and access to simple, low-cost solutions for processing biodegradable waste at the source. The community service program aimed to address this gap by educating vocational agriculture students on how to transform kitchen waste into eco-enzyme, a multipurpose organic liquid produced through fermentation. The program used a participatory method that combined presentations, discussions, and hands-on practice to enhance student engagement and learning outcomes. Students learned how to measure, mix, and monitor the production of eco-enzymes using locally available materials, such as fruit scraps, water, and brown sugar. The impact was measured using a pre- and post-assessment questionnaire, which was analyzed through the Mann–Whitney U test. This analysis revealed significant improvements in student knowledge, attitude, and willingness to apply eco-enzyme techniques. Field observations confirmed that students responded enthusiastically, showing curiosity and initiative during the practical sessions. The results suggest that integrating experiential environmental education into vocational school programs can help bridge knowledge gaps and inspire sustainable behavior among young people. This initiative demonstrates that empowering students through hands-on environmental learning not only improves understanding but also cultivates long-term ecological responsibility. Schools and policymakers should consider incorporating eco-enzyme training modules into the agricultural curriculum to support local waste reduction efforts and promote sustainability at the grassroots level.